The Practicality of Virtual Reality Applications in Education: Limitations and Recommendations - Al Farsi, Ghaliya; Azmi, Mohd Yusof; Wan Jumani, Fauzi; Mohd Ezanee, Rusli; Malik, Sohail Iqbal; Tawafak, Ragad M.; Mathew, Roy; Jabbar, Jasiya (jonuns.com, 2021)
The use of virtual reality applications has grown tremendously in recent years. Virtual reality applications in the education domain have many benefits: they engage students, arouse students' curiosity, ease the communication of information, and motivate the students to improve their learning and performance. Despite literature showing that there has been a clear development in the education domain that shows improvement in students' learning skills, its application in Higher Education Institutions (HEIs) is limited to certain courses and fields. Furthermore, there has also been under-utilization and misutilization of virtual reality applications. Thus, the primary research question in this paper would be what the issues of the practicality of virtual reality applications for HEIs are. This paper aims to look at practicality issues to understand why VR is underutilized, particularly in HEIs. A review of the literature based on seventeen papers published between 2010 and 2020 taken from databases such as Science Direct, Ebscohost, and Scopus has found that despite the positive continuous intention to use VR applications, there are many issues regarding their practicality, such as the affordability of VR application tools, the technology-savviness of instructors, as well as the sustainability of VR use. This paper is significant as it explored and identified the practical issues of why VR applications are underused and provides practical suggestions to overcome these issues of practicality. It is hoped that HEIs would not allow these limitations to hinder the use of VR applications so that the students of this era, who are digital natives, would learn and perform better with VR applications; thus, making the use of VR applications in HEIs more widespread.